Quantitative analysis of the effects of project-based learning on vocabulary recall - Ortega Yanez, Fausto David (2023)
Reviews of qualitative studies about Project Based Learning suggest that it positively affects the outcome of English Language Learners (Golden et al., 2014). ProjectBased Learning provides high speaking time with English-proficient students (Campbell, 2012), integrates content and skills (Beckett, 2002), and increases motivation (Beneke and Ostrosky, 2009). Unfortunately, it was impossible to locate any rigorous quantitative empirical evidence supporting these claims. According to Farhady (2006), the experimental design is best to measure the effectiveness of new methodologies. Therefore, it was essential to investigate how Project Based Learning affects the academic achievement of English Language Learners by conducting empirical research. Vocabulary provides the necessary input to develop other skills such as reading and writing and making speaking fluency possible (Nation & Waring, 1997). Therefore, we seek to investigate if project-based Learning can contribute to enhancing vocabulary recall. A series of pretests and posttests measure the effectiveness of Project-Based Learning on vocabulary recall using a t-test to compare the results. Such a design required an experimental approach using two groups of participants. Finally, we created a guide of suggestions for using projectbased Learning to enhance vocabulary recall.